Interaction effect of donor age and body weight on superovulation and embryo production performance in goats - RAHMAN, M R; RAHMAN, M M; KHADIJAH, W E WAN; ABDULLAH, R B (The Indian Journal of Animal Sciences, 2016)
The experiment was conducted to evaluate the interaction effect of age and body weight (BW) on ovarian responses in follicle stimulating hormone (pFSH) superovulated doe. Does (40) were divided into groups 1 (2–4 years old and 15–25 kg BW), 2 (2–4 years old and 26–35 kg BW), 3 (5–7 years old and 15–25 kg BW) and 4 (5–7 years old and 26–35 kg BW). Oestrus was synchronized by inserting a controlled internal drug release (CIDR) and a single injection of prostaglandin F2α. Does were administered 5 mg pFSH/kg BW, twice a day through 6 decreasing dosages. All does of Group 2 showed oestrus signs, while 70, 70 and 80% of does of group 1, 3 and 4 showed oestrus, respectively. Natural mating was carried out when does showed oestrus. Ovarian responses were evaluated on Day 7 after CIDR removal. Group 2 produced higher number of corpus luteum than other groups. Average number of embryo production was higher in group 2 than that in groups 1, 4 and 3. Transferable embryo production was higher in group 2 than in groups 4 and 1. Group 3 did not produce any transferable embryos. Numbers of anovulatory follicles per doe were similar in group 2 and 4, but higher than that in group 1 and 3 and did not show any differences. Does in group 2 gave higher number of embryos than other groups, indicating that donor age and BW interaction is an important consideration for superovulation in goats.